University Students’ Critical Literacy in Their Speaking Skill - Arjulayana arjulayana (IAIN Syekh Nurjati Cirebon, 2023)
Speaking is the way to communicate, to say something, to express ideas, and to make speech orally. Speakers say something based on the content they have, and the content is produced when speakers have critical literacy. The purpose of this research is to find out and to investigate critical literacy demonstrated by students in their speaking performance. This research used qualitative approach with descriptive analysis method. The samples of this research were 5th semester of 25 students from University of Muhammadiyah Tangerang. In collecting the data, the researcher used speaking test and interview with purposive sampling technique. The researcher found out that all critical literacy aspects occurred in the students’ content through their speech. High students presented more critical literacy’s indicator than medium and low students. High students had good preparation and achieved all critical literacy indicators, middle students had a little preparation and achieved half of critical literacy indicators, low students were lack of preparation and did not achieve critical literacy indicators. This study suggested that all stages of speaking process, especially pre-speaking stage, can help students to speak and stimulate their critical literacy better.